Reproductive Health Knowledge and Services Utilization among Rural Adolescents in Rwamagana District, Rwanda - Patricie Mukandagano; Monica Mochama; Erigene Rutayisire (Journal of Public Health International, 2022)
This study aims to assess reproductive health knowledge and services utilization among adolescents from Rwamagana District. A community based cross-sectional study was carried out in Rwamagana district. A sample of 392 adolescent aged 15-19 participated in the study. Simple random sampling was used to select respondents. Data was collected by using a questionnaire adopted from previous studies. Data was checked for completeness, cleaned, coded and entered into excel sheet, and then exported to SPSS version 22.0 for further analysis. Frequencies and percentage was used to summarize descriptive statistics. To determine the association between different factors associated with reproductive health knowledge and services utilization, a logistic regression model was employed. Ethical clearance was obtained from the Ethical committee of Mount Kenya University. It was observed that the majority of adolescents in Rwamagana District knew the sign of maturity. Overall the majority of adolescents 91.8% in Rwamagana District had good knowledge about reproductive health services. The majority of adolescents in Rwamagana District (66.8%) had ever utilized reproductive health services at health facility. It was observed that adolescents who live with their parents were more likely to use reproductive health services compared to those who do not live with parents (aOR=2.161, 95%CI: 1.162-4.021, p=0.015). Moderate reproductive health services utilization was observed among adolescents. There is a need to increase adolescent’s awareness on the available services at health facilities.
Keywords: Adolescents